Влияние водородной атмосферы на свойства пленки оксида алюминия на титане BT1-0; Журнал технической физики; Т. 89, № 4 - Сыпченко В. С. Владимир Сергеевич; Ван Цайлунь; Никитенков Н. Н. Николай Николаевич; Тюрин Ю. И. Юрий Иванович; Сигфуссон Т. И. Торстеинн Инги; Филимонова В. С. Валерия Сергеевна (2019, 2019)
Заглавие с экрана